Assuan, Ägypten. Epigraphie, Bau- und Nutzungsgeschichte des Klosters Deir Anba Hadra. Die Arbeiten des Jahres 2016 bis Juni 2017 - Richter, Sebastian (e-Forschungsberichte des DAI, 2017)
Deir Anba Hadra, formerly known as Monastery of St. Simeon, is situated on the West bank of Aswan, 1 km inland on the gebel above a wadi. Its foundation is connected to local traditions about Hatre, a hermit saint and bishop of Aswan in the later 4th century AD whose hermitage seems to have been localized here. The project investigates the usage history of Deir Anba Hadra from its beginnings in the 7th–8th century up to the latest evidence of Christian-Coptic, Christian-Arabic and Muslim visitors’ inscriptions in the Mamluk period. In the course of work a new documentation of the architecture and building history of the church and the workshops as well as a comprehensive documentation of the epigraphic evidence and the wall paintings have been made.